Suppressor of Fused is Critical for Maintenance of Neuronal Progenitor Identity During Corticogenesis - Yabut, Odessa R. (Cell Rep, 2015)
Proper lineage progression and diversification of neural progenitor cells (NPCs) ensures the generation of projection neuron (PN) subtypes in the mammalian neocortex. Here we show that Suppressor of Fused (Sufu) controls PN specification by maintaining the identity of NPCs in the embryonic neocortex. Deletion of Sufu in NPCs of the E10.5 mouse neocortex led to improper specification of progenitors and a reduction in intermediate progenitors (IP) during corticogenesis. We found that Sufu deletion resulted in unstable Gli2 and Gli3 activity leading to the ectopic activation of Sonic hedgehog (Shh) signaling. The role of Sufu in maintaining progenitor identity is critical at early stages of corticogenesis since deletion of Sufu at E13.5 did not cause similar abnormalities. Our studies revealed that Sufu critically modulates Shh signaling at early stages of neurogenesis for proper specification and maintenance of cortical NPCs to ensure the appropriate generation of cortical PN lineages.